2022
DOI: 10.1177/26323524221131581
|View full text |Cite|
|
Sign up to set email alerts
|

The impacts of partnering with cancer patients in palliative care research: a systematic review and meta-synthesis

Abstract: Background: Palliative care (PC) is an added layer of support provided concurrently with cancer care and serves to improve wellbeing and sustain quality of life. Understanding what is meaningful and a priority to patients, their families, and caregivers with lived experience of cancer and PC is critical in supporting their needs and improving their care provision. However, the impacts of engaging cancer patients within the context of PC research remain unknown. Objective: To examine the impacts of engaging ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(176 reference statements)
0
4
0
Order By: Relevance
“…In Paolucci et. al’s [ 19 ] systematic review of patient engagement in palliative care research, they only identified three studies that engaged patients with lived experience of cancer as partners in the health research process. In Abelson et.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Paolucci et. al’s [ 19 ] systematic review of patient engagement in palliative care research, they only identified three studies that engaged patients with lived experience of cancer as partners in the health research process. In Abelson et.…”
Section: Discussionmentioning
confidence: 99%
“…Patients newly diagnosed with lung cancer in the study region are served by publicly funded [ 19 ] medical and radiation oncology outpatient clinics at a tertiary cancer centre, which serves 1.4 million people in a zone (Calgary, Alberta, Canada) including a metropolitan city, surrounding towns, rural areas and First Nations territories. A Lung Tumour Group Coordinator (nurse) triages new referrals to six lung-focused oncologists, and each oncologist clinic has one oncology nurse.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Contributors get the satisfaction that they are offering something back to society. It can give a sense of belonging to something important and giving to the greater good [ 16 ]. Making a positive difference in research that may ultimately lead to improvement in patients’ lives is a fundamental reason why many public members get involved with research in the first place.…”
Section: What Are the Benefits Of Public Engagement?mentioning
confidence: 99%